Using polarimetric observations to detect and quantify the three-dimensional radiative transfer effects in passive satellite cloud property retrievals: Theoretical framework and feasibility study. (May 2020) - Rajapakshe, Chamara; Zhang, Zhibo
Highlights: A new method to detect 3-D radiative transfer effects in passive cloud property retrievals. Theoretical basis with the aid of idealized 1-D cloud fields. Strong illuminating effects can be detected, and large COT biases can be corrected. Both radiometric and polarimetric image of the same cloud target are required.